2021
DOI: 10.3389/fgene.2021.761791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Germline Structural Variant Calling Methods for Nanopore Sequencing Data

Abstract: Structural variants (SVs) are genomic rearrangements that involve at least 50 nucleotides and are known to have a serious impact on human health. While prior short-read sequencing technologies have often proved inadequate for a comprehensive assessment of structural variation, more recent long reads from Oxford Nanopore Technologies have already been proven invaluable for the discovery of large SVs and hold the potential to facilitate the resolution of the full SV spectrum. With many long-read sequencing studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
7
18
0
Order By: Relevance
“…We found that similar tool combinations (especially cuteSV, followed closely by Sniffles2 and dysgu after minimap2 alignment) had superior performance across all the simulated datasets. The findings are in line with a recent study reporting that cuteSV performed better than other tested SV tools such as Sniffles1, SVIM, and pbsv for precision and recall at both SV calling and genotyping in human datasets (Bolognini and Magi, 2021). Increasing coverage improved recall and F1-scores for all tested SVs calling combinations, confirming that the probability of detecting quality SVs increases with more sequencing coverage (Jiang et al, 2021).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We found that similar tool combinations (especially cuteSV, followed closely by Sniffles2 and dysgu after minimap2 alignment) had superior performance across all the simulated datasets. The findings are in line with a recent study reporting that cuteSV performed better than other tested SV tools such as Sniffles1, SVIM, and pbsv for precision and recall at both SV calling and genotyping in human datasets (Bolognini and Magi, 2021). Increasing coverage improved recall and F1-scores for all tested SVs calling combinations, confirming that the probability of detecting quality SVs increases with more sequencing coverage (Jiang et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…Many of the SV detection tools are benchmarked primarily on human/animal datasets, (Bolognini and Magi, 2021; Coster et al, 2019; Dierckxsens et al, 2021; Jiang et al, 2020; Jiang et al, 2021; Zhou et al, 2019), however the complexity and different SV profiles of crop plant genomes might bring unique challenges. Therefore, to guide the design of large-scale long-read re-sequencing studies, this study performed comprehensive benchmarking of popular SV calling tools with a focus on tool performance at lower sequencing coverage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b , CuteSV reproducibly showed higher recall and precision scores than Sniffles in the detection of DELs. This result is concordant with previous benchmark studies 41 , 43 , and we therefore decided to utilize the CuteSV algorithm. Utilizing this algorithm, we next compared the precision and recall scores of activated T cells and LCLs.…”
Section: Resultssupporting
confidence: 89%
“…7 b–i). Our results that a slight increment in performance after depth of coverage > 20× were also found in a prior study of SV calling methods using nanopore sequencing data [ 44 ].
Fig.
…”
Section: Resultssupporting
confidence: 87%